Influence of the instability of chip formation and preheating of work on tool life in maching high temperature resistant steel and titanium alloys - Amin, A. K. M. Nurul; N. V., Talantov (1986)
It has been established by experimental investigations that machining of high temperature resistant steel and titanium alloys with cemented carbide tools is accompanied with inherent instability of chip formation. This type of instability causes micro and macro chipping of the tool tip and consequently decreases tool life to a great extent. It has been also established that tool life can be greatly increased by preliminary heating of the work up to a certain optimum temperature, which varies with work and tool materials and conditions of cut.